2009
DOI: 10.1080/02763860903249076
|View full text |Cite
|
Sign up to set email alerts
|

“Hidden Treasures”: Librarian Office Hours for Three Health Sciences Schools

Abstract: The changing needs of students and faculty have prompted UNC Chapel Hill's Health Sciences Library to reconsider the delivery of library services. Several years of outreach and office hours have yielded an array of "hidden treasures," or secondary outcomes, of both online and in-person office hours. The online office hours are tailored for the Schools of Medicine, Pharmacy, and Public Health. This article examines the benefits that go beyond simple consultation statistics and encompass more qualitative aspects… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2011
2011
2017
2017

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(11 citation statements)
references
References 5 publications
0
11
0
Order By: Relevance
“…They found that onsite weekly office hours increased reference transactions from users by 28% and doubled liaison contacts with users in that setting. A study by Handler, Lackey, and Vaughan also documented that outreach and office hours, both in-person and online, yielded more contact between users and librarians and fostered good will, partnerships, and peer relationships between the library and their clients at three health sciences schools (10). The efforts at THSL build on this evidence base and support findings of the effectiveness of in-person and online outreach.…”
Section: Office Hours On Locationmentioning
confidence: 75%
See 1 more Smart Citation
“…They found that onsite weekly office hours increased reference transactions from users by 28% and doubled liaison contacts with users in that setting. A study by Handler, Lackey, and Vaughan also documented that outreach and office hours, both in-person and online, yielded more contact between users and librarians and fostered good will, partnerships, and peer relationships between the library and their clients at three health sciences schools (10). The efforts at THSL build on this evidence base and support findings of the effectiveness of in-person and online outreach.…”
Section: Office Hours On Locationmentioning
confidence: 75%
“…Although the existence of an embedded librarian is not a unique factor and this concept has been frequently mentioned in library literature (9,10), the use of an electronic monthly newsletter is an innovative delivery method for providing services to the members of a remote location that combines hospital and academic needs. When transferring these strategies from an academic health library to a hospital library setting, it is important to consider the major differences between the two contexts.…”
Section: Resultsmentioning
confidence: 99%
“…In another study, after fearing that their user communities were "losing touch" with the library, Freiburger and Kramer, two librarians at the Arizona Health Sciences Library, began a successful office hour program that led to not only increases in annual literature search request numbers, but also invitations to participate in grants and instruction (7). Handler et al, writing about their office hour experience at the University of North Carolina at Chapel Hill's Health Sciences Library, listed a number of secondary benefits associated with office hours, including increases in contacts and interactions, goodwill, and in the ability to build and cultivate long-term relationships with clients (8).…”
Section: Literature Reviewmentioning
confidence: 98%
“…Identifying an appropriate name is important, particularly if the service is to align with an already existing office hour, reference, or outreach service. Marketing is acknowledged as an important component of a successful implementation, and case studies list e-mails, faculty and department meetings, instruction sessions, LCD displays, and print handouts and signage as possible promotional methods (6)(7)(8)(9). Although mentioned less frequently in the literature, obtaining buy-in from key personnel in the unit is essential, because it is the key personnel who are likely to provide the librarian with the equipment and space necessary to run the office hours and to help facilitate the librarian's integration into the unit's workflow.…”
Section: Literature Reviewmentioning
confidence: 99%
“…17 Early embedded librarians have been pleased to discover that their attempts to increase transactions with patrons bring the unexpected benefits of collaboration and integration with the target department. 18 More recent embedded programs have set heightened collaboration and integration as goals from the outset. 19 While individual librarians may be satisfied with meeting these goals, the library organization generally sees interaction, collaboration, and integration as steps to the all-encompassing goal of demonstrating the value of the library to the campus community.…”
Section: Goals Of Embedded Librarianshipmentioning
confidence: 99%